Faktor-Faktor Yang Berhubungan Dengan Gangguan Siklus Menstruasi Pada Wanita Usia Subur Di Wilayah Kerja Puskesmas Mandiangin Bukittinggi Tahun 2014 - Susanti, Evi; Heppy, Fredia (Jurnal Kesehatan - STIKes Prima Nusantara, 2015)
This study originated from the phenomenon of women's lack of attention to the menstrual cycle disorders, reproductive health-related, and therefore the presence of this research will be the concern of every woman's reproductive health. Disorders of the menstrual cycle is an important indicator which shows the function of the reproductive system disorders that can be associated with an increased risk of various diseases such as cervical cancer and infertility. Initial survey in Dublin City Health Office showed that the majority of women of childbearing age are in Work Area Health Center Mandiangin. The study aims to determine the factors associated with impaired menstrual cycle in women of childbearing age. This research was conducted at the Work Area Health Center Mandiangin, cross sectional study design, April to October 2014, population in this study were women of reproductive age 15-44 years in the Work Area Health Center Mandiangin as 556 after being put into a formula of simple random sampling of 85 samples, Data were processed and analyzed by computer. The results showed that most respondents experienced menstrual cycle disorders (65.9%), the majority of respondents experience stress (81.6%), most respondents weight premises at risk (78.4%), the majority of respondents had no good diet (81 , 6%), and the majority of women of childbearing age with activities that are not at risk (66.2%). Based on the variables studied, there are three variables that had a significant relationship to the menstrual cycle disturbances in women of childbearing age are stress, weight, and diet. While physical activity variables were not related. Expected to health center staff Mandiangin especially midwives to conduct outreach and counseling to women of childbearing age that every woman will know her menstrual cycle in order to improve knowledge of women of childbearing age about the normal menstrual cycle